Experiences of loveLife Trust telephone counsellors about the EWP employed within Gauteng - Mpekana, Rebecca (University of the Witwatersrand, Johannesburg, 2022)
Globally, most Non-Profit Organisations (NPOs) do not prioritise employee wellness programmes (EWPs). NPOs’ funding is often allocated for rendering their primary programmes rather than improving their employees’ wellness. Employees in NPOs are left to devise their own means to best cope with work-related stress and challenges. Some employees rely on support from community-based organisations or their colleagues. loveLife Trust is a South African NPO that operates nation-wide. loveLife Trust recently introduced EWP to be utilised by its employees who are telephone counsellors. As of year 2022, loveLife Trust employs about 12 telephone counsellors. The loveLife Trust counsellors render psychological support to youth country-wide. Dealing with the youth’s presenting problems exposes the telephone counsellors to burnout and anxiety. This study aimed to explore how telephone counsellors experience the loveLife Trust EWP service. This was a qualitative study that allowed the participants to openly share their views. The total participants for this study were 12 telephone counsellors who were working on the toll-free line which is based in Gauteng. In addition, two key informants; the team supervisor and an EWP account manager, were interviewed. All participants were interviewed through ZOOM Cloud Meetings. A qualitative interview schedule that was guided by open-ended one-on-one interview questions was used for data collection. Thematic data analysis was used to derive different themes for the study. The aim of the study was to explore the experiences of telephone counsellors on EWP at loveLife Trust. The telephone counsellors are based in the call centre in Gauteng. The study revealed that telephone counsellors have not utilised the EWP as a way of support. The telephone counsellors prefer collegial support for taking care of their wellness. To spark interest amongst telephone counsellors to utilise the service, loveLife management should prioritise EWP awareness.
MA in Social Work by coursework and research report in Occupational Social WorK, 2022
Keywords: Employee assistance programme; Employee wellness programme; Telephone counsellors; Occupational social work; loveLife Trust; SDG-3: Good health and well-being; SDG-17: Partnerships for the goals